Pengaruh Pernikahan Dibawah Umur Terhadap Keharmonisan Keluarga Di Kota Gorontalo - Panabulu, Krisdeyanti; Dungga, Weny Almoravid; Moha, Mohamad Rivaldi (CV. ITTC INDONESIA, 2023)
Married life through marriage is one of the pages of life that every human being will go through. That's when the maturity of the husband and wife is highly demanded in order to achieve success in building a household ark. Underage marriage is a marriage carried out by a man and a woman whose age has not yet reached the age limit for marriage, where the age limit for marriage is regulated in law. The age for marriage according to Law Number 16 of 2019 Article 7 paragraph (1), marriage is only permitted if a man and a woman have reached the age of 19 (nineteen) years. The age limit for marriage is expected so that the couple is better prepared to undergo a household ark. Harmony in the household is the hope of every married couple who get married. A harmonious family can be seen from a family that is harmonious, happy, full of love and conflicts rarely occur in the family. However, the reality that occurs in the underage marriage community has an impact on harmony in marriage, where the desire to get married but has not reached psychological maturity or can be said to be not old enough causes problems in the household and causes seriousness in carrying out the marriage. This phenomenon shows that underage married couples are still unstable in dealing with problems. This study aims to describe the household life of married couples related to the influence of their underage marriage on the harmony of their household, the type of research used is field research (Field Research), and the nature of this research is descriptive qualitative. This study used interview and documentation data collection techniques. The influence of underage marriage on household harmony felt by husband and wife in Gorontalo City has an effect on harmony in their household because a person who is not old enough to get married causes many impacts on harmony in the household. Underage marriage is one of the reasons why harmony does not exist in the household, besides that couples who marry at a young age are also not ready psychologically and socio-economically. In general, they do not have permanent jobs so that economic difficulties can trigger problems in the household.